Antioxidant properties and production of monacolin K, citrinin, and red pigments during solid state fermentation of purple rice (Oryzae sativa) varieties by Monascus purpureus - Prodpran Pengnoi (2018)
This study aims to evaluate the effects of various purple rice varieties on the production of monacolin K, citrinin, and red pigments by Monascus purpureus CMU002U (UV-mutant strain) and their antioxidant properties. The lowest value of citrinin concentration (132 ppb) was found in the SSF of the Na variety, which passed the standards of Japan, Taiwan, and European Union. The high monacolin K (13 482 ppm) and red pigment (388.25 units/g) levels were obtained from the fermented Doi Muser variety. The lowest IC50value of the DPPH assay was found in the extract of fermented Doi Saked variety. An investigation of temperature shifting of the SSF for the Doi Muser variety indicated that the incubation at 30°C for 5 days, followed by 25°C until 30 days, yielded the highest value of monacolin K (35 292 ppm) production. These results demonstrated that fermented purple rice has a high potential to be developed as a new food supplement.